Conceptualisations and analyses of distrust and mistrust in news media: Reviewing research from a decade of distrust - Jakobsson Peter; Stiernstedt Fredrik (Nordicom Review, 2025)
This article provides a comprehensive review of research on distrust towards news media and journalism, a topic that has gained significant attention in recent years due to declining institutional trust and the rise of political disinformation. We analyse existing literature focusing on how media distrust has been studied and conceptualised, its explanations, and its consequences. We highlight the conceptual diversity and methodological plurality in the field, noting the varied definitions and operationalisations of distrust, as well as the dominance of quantitative approaches alongside significant qualitative contributions. The complex relationship between distrust in the media and democracy is also explored, revealing conflicting evidence on whether distrust leads to news avoidance and reduced political engagement or fosters critical media consumption and political engagement. The review underscores the need for clearer definitions and typologies of distrust, supplementing dichotomous operationalisations of trust/distrust with ones that capture distrust as a multidimensional phenomenon, with each dimension having different antecedents and consequences.